2004
DOI: 10.1002/ajmg.c.30031
|View full text |Cite
|
Sign up to set email alerts
|

Calcium pump disorders of the skin

Abstract: The causes of Darier disease (DD) and Hailey-Hailey disease (HHD) have eluded clinicians and scientists for more than 60 years. DD is characterized by loss of adhesion between suprabasal epidermal cells associated with abnormal keratinization, while loss of epidermal cell-to-cell adhesion is predominant in HHD. The genes for both conditions have recently been identified using candidate positional cloning approaches. The gene for DD (ATP2A2) encodes a calcium transport ATPase of the sarco (endo)plasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 71 publications
(80 reference statements)
0
65
0
3
Order By: Relevance
“…The co-expression of hSPCA2 and hSPCA1 could help to explain the relatively high contribution of thapsigargininsensitive Ca 2ϩ accumulation in the Golgi of keratinocytes (33) and lung-derived 16HBE14oϪ cells (34). The proper function of the secretory pathway in keratinocytes may be crucial for correct delivery of cell adhesion components (15). The fact that hSPCA2 is not able to compensate for the decreased level of hSPCA1 in keratinocytes of Hailey-Hailey disease patients may suggest a specific function for this pump distinct from that of hSPCA1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-expression of hSPCA2 and hSPCA1 could help to explain the relatively high contribution of thapsigargininsensitive Ca 2ϩ accumulation in the Golgi of keratinocytes (33) and lung-derived 16HBE14oϪ cells (34). The proper function of the secretory pathway in keratinocytes may be crucial for correct delivery of cell adhesion components (15). The fact that hSPCA2 is not able to compensate for the decreased level of hSPCA1 in keratinocytes of Hailey-Hailey disease patients may suggest a specific function for this pump distinct from that of hSPCA1.…”
Section: Discussionmentioning
confidence: 99%
“…Hailey-Hailey disease is an autosomal dominant skin disorder that is characterized by suprabasal acantholysis of keratinocytes, resulting in epidermal blister formation. Up till now a total of 70 different mutations have been described in Hailey-Hailey disease patients (15). These mutations are scattered throughout the entire gene with no apparent clustering.…”
Section: ؉mentioning
confidence: 99%
“…In contrast to SERCAs, SPCAs are also equipped to transport Mn 2þ and thus supply this essential trace metal to the Golgi lumen. A number of comprehensive reviews have been published recently by our group Vangheluwe et al 2009) and by others (Dhitavat et al 2004;Foggia and Hovnanian 2004;Brini and Carafoli 2009). …”
Section: Spcasmentioning
confidence: 92%
“…In humans, it has been suggested that HHD and Darier disease may result from defective processing and trafficking of desmosomal components (63). In the case of HHD, this mechanism seems unlikely, since desmosomes and other cell surface structures appeared normal in null mutant mice.…”
Section: Squamous Cell Tumors In Spca1 Heterozygous Micespca1mentioning
confidence: 99%